Verification methods of a programmer’s knowledge and skills - Hajduk, Paweł; Wieruszewski, Norbert; Skublewska-Paszkowska, Maria (Journal of Computer Sciences Institute, 2018)
The article describes currently utilized methods of a programmer’s knowledge verification and skills. The research consisted of creating custom solution which was an application implementing chosen methods and carrying out test with the participation of programmers having various levels of experience, knowledge and skills. Effectiveness of assessment, reliability and verification time were evaluated based on an analysis of the results received from the research